Validity of Serum Pepsinogen I/II Ratio for the Diagnosis of Gastric Epithelial Dysplasia and Intestinal Metaplasia during the Follow-Up of Patients at Risk for Intestinal-Type Gastric Adenocarcinoma - Dinis-Ribeiro, Mário (Neoplasia Press Inc., 2004)
A cohort of individuals (n = 136) with lesions as severe as atrophic chronic gastritis (ACG) was cross-sectionally evaluated for the validity assessment of pepsinogen I (PGI) and pepsinogen II (PGII) serum levels for the diagnosis of intestinal metaplasia (IM) and gastric dysplasia. PGI/PGII ratio [median (range)] was 4 (0.5–7.5) in patients with ACG (n = 35); 4.6 (1.9–6.8) in type I IM (n = 18); 4.2 (1.4–5.9) in type II or type III IM limited to the antrum and incisura (n = 20); 2.4 (0.4–5.6) in extensive incomplete IM (n = 38); and 1.3 (0.4–6.4) in low-grade dysplasia (n = 23) (P = .002). Using histopathologic data as a reference test, the area under the receiver operating characteristic curves (CI 95%) was 0.73 (0.64–0.82) for extensive IM, 0.72 (0.58–0.85) for the diagnosis of dysplasia, and 0.81 (0.66–0.95) for the diagnosis of high-grade dysplasia. Using a PGI/PGII ratio of ≤3 as the cutoff for dysplasia diagnosis, the sensitivity was 70% (62–78%), the specificity was 65% (57–73%), and the negative predictive value estimates were over 90%. No differences in PG levels according to age or gender were observed. Helicobacter pylori did not significantly influence validity measurement estimates. PGI/PGII serum level ratio can be used even in the management of patients with a high a priori probability for a positive test. It may be useful for the exclusion of more advanced lesions (extensive IM and neoplastic lesions).